2013
DOI: 10.1002/alr.21154
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Staphylococcus aureus: the Trojan horse of recalcitrant chronic rhinosinusitis?

Abstract: Clinical and microbiological relapse of disease following ESS is significantly associated with intracellular S. aureus. Evidence suggests that this disease association is independent to surface biofilm status. Intracellular bacteria should be taken into consideration when designing novel treatment strategies to lessen the chance of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 40 publications
1
68
0
2
Order By: Relevance
“…4,5,8,10,20 These have consistently observed ICSA in CRS patients with differing prevalence in the different CRS patient populations. These discrepancies can be attributed to differences in ICSA detection strategies, the definition of CRS phenotypes, and the use of CRS patient tissue types.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…4,5,8,10,20 These have consistently observed ICSA in CRS patients with differing prevalence in the different CRS patient populations. These discrepancies can be attributed to differences in ICSA detection strategies, the definition of CRS phenotypes, and the use of CRS patient tissue types.…”
Section: Discussionmentioning
confidence: 91%
“…Nasal polyps were 1 of the first tissue types to be identified to have ICSA, 4 although they have been subsequently demonstrated in nonpolypoid mucosa of CRSsNP patients. 8 Corriveau et al 9 showed no difference in ICSA prevalence between CRSsNP, CRSwNP, and control groups, whereas studies by Tan et al 10 showed that ICSA was most prevalent in patients with CRSwNP. Interestingly, a subsequent study by Kim et al 8 reported a greater percentage of ICSA in CRSsNP although no statistically significant difference was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations